On some faraway beach : the life and times of Brian Eno - Sheppard, David (Chicago Review Press, 2009)
From an idiosyncratic childhood in a sleepy British market town to the top of the international pop charts, this first critical examination of the life of Brian Eno charts a lengthy and colorful journey. Interviews with many key collaborators?such as David Byrne, Robert Wyatt, John Cale, Bryan Ferry, and Gavin Bryars?along with input from Brian and his wife, Anthea, illuminate the man and his ideas and how he retained an edge and maintained independence. This sonic alchemist to the stars has contributed to the most challenging and critically revered w
Keywords: Eno, Brian, : 1948-; Rock musicians; Sound recording executives and producers